3D MODELING OF HISTORICAL DOGER CARAVANSARIES BY DIGITAL PHOTOGRAMMETRY - M. Yakar (Selçuk Üniversitesi, Mühendislik-Mimarlık Fakültesi, Harita Mühendisliği Bölümü, Turkey) (Copernicus Publications, 2018)
Caravansaries are sort of bigger khan that established on the busy trade roads to provide any kind of supplies but essentially all Caravansaries on Anatolia are established for caravans' accommodations which are passing through on caravan rout. After the Turks had chosen being Muslim, the land that Islam religion spread on it has expanded. As a result of this expansion it is required a safe route for trade caravans. During the ruling time of Seljuk's Empire, Caravansaries took the most advanced form. Sultans of the Seljuk's Empire were aware of importance of trade and economy. That's why they established Caravansaries near marines, between the important trade centers and on Anatolian lands which is a bridge between East and West. But these trade routes has changed at the time of Ottoman Empire. Many of the historical places in the world have been totally or partly destroyed by natural events and human activities such as earthquake, flood and fire until the present day and still going on. Documentation is essentially required for protection and restoration these historical places and photogrammetry is one of the most effective method for documentation of cultural heritages. In this study, it is aimed to get 3D models of Doger Caravansaries which is established in Afyonkarahisar for relief and advertising. Doger Caravansaries was built in 15. Century at Sultan II Murat eras but the exact date of building is not known. The structure has rectangular plan in width. The total length of it is 56.50 in meters. The Caravansaries is consisting of attached two parts. The first part has two floors. There are pointed arched niches in the two sides of the wall and there are windows (iron barred) in the middle of the each niche. The door is fillet low arched. First floor rises on four elephant foot columns and ten other small columns. Short sides are covered by two each cross squinch and the other parts with barrel vault. There is a ladder with only ten remain levels opposite the main gate. Today, it has been cancelled to reach upstairs. The underside of the satires is empty. There are two loophole windows at the both two short side. The columns that are near the long walls are bounded each other with arches and overlaid with cross squinches. The rooms in the second floor have domes. One of these rooms was arranged as prey room. The second part of Caravansaries is single storey and walls made of rubble. There are four columns inside the room and they bounded with arches. Back side of the rooms were destroyed by earth quake and restored. This restoration was not appropriate with its original plan but the good one is that the Caravansaries was saved from totally comedown. It is aimed to survey Doger Caravansaries Photogrammetricaly and generate 3D model covered by real tissues. In this study, South NTS-352 Total Station is used to constitute a closed polygon with 6 point. The coordinates of polygon points are calculated by distance and direction measurements. Levelling was carried out for determining the height of polygon points. Photographs was taken by Nikon D7000 camera. 3D model and faces were created in Photomodeler software.